2018
DOI: 10.18632/oncotarget.25128
|View full text |Cite
|
Sign up to set email alerts
|

EZH2 inhibitors sensitize myeloma cell lines to panobinostat resulting in unique combinatorial transcriptomic changes

Abstract: Multiple myeloma (MM) remains a largely incurable hematologic cancer due to an inability to broadly target inevitable drug-resistant relapse. Epigenetic abnormalities are abundantly present in multiple myeloma and have increasingly demonstrated critical roles for tumor development and relapse to standard therapies. Accumulating evidence suggests that the histone methyltransferase EZH2 is aberrantly active in MM. We tested the efficacy of EZH2 specific inhibitors in a large panel of human MM cell lines (HMCLs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
2
23
0
Order By: Relevance
“…Overall, targeting the PHF19-PRC2-EZH2 complex could represent a novel therapeutic strategy for MM treatment. Indeed, EPZ-643 and GSK-126, known as EZH2 inhibitors, were shown to sensitize MM cells to HDAC inhibitor panobinostat, favoring MM cell apoptosis and reducing MM cell survival [ 55 ]. Similarly, recent studies have demonstrated how PRC2 inhibitors were able to inhibit MM tumorigenicity [ 54 , 55 ].…”
Section: Epigenetics In Multiple Myeloma: Dna Methylation Histonementioning
confidence: 99%
“…Overall, targeting the PHF19-PRC2-EZH2 complex could represent a novel therapeutic strategy for MM treatment. Indeed, EPZ-643 and GSK-126, known as EZH2 inhibitors, were shown to sensitize MM cells to HDAC inhibitor panobinostat, favoring MM cell apoptosis and reducing MM cell survival [ 55 ]. Similarly, recent studies have demonstrated how PRC2 inhibitors were able to inhibit MM tumorigenicity [ 54 , 55 ].…”
Section: Epigenetics In Multiple Myeloma: Dna Methylation Histonementioning
confidence: 99%
“…These mechanisms may involve microRNA silencing of TAZ, as has been shown in other cancers, 61 or other epigenetic modifiers. In several studies, including some genome-wide screens, TAZ was found to be upregulated in response to silencing the histone demethylase JMJD1a 62 or treatment with epigenetic inhibitors such as BTZ, 63 enhancer of zeste homolog 2 (EZH2) inhibitors, 64 the panHDAC inhibitor Pano, 65 and the BET inhibitor JQ1. 66 We show that the TAZ promoter is specifically methylated ( Figure 2C) and that globally inhibiting DNMTs increased TAZ expression in HMCLs ( Figure 5A-D).…”
Section: Discussionmentioning
confidence: 99%
“…Synergistic or re-sensitizing effects between EZH2 inhibitors and traditional cytotoxic anti-cancer drugs have been seen [155,156]. In view of the abundantly present epigenetic abnormalities of H3K27 tri-methylation and histone acetylation, a couple of studies have combined EZH2 inhibitors with different HDAC inhibitors for the treatment in MM [157,158] and B cell lymphoma cells [54,123,159,160], and favorable therapeutic coordination were observed. Dual-targeting of MYC and EZH2 has been employed to disrupt MYC-EZH2 oncogenic axis in aggressive B cell lymphoma cells [51].…”
Section: Combinatorial Targeting With Other Chemotherapeutic Agentsmentioning
confidence: 99%